Reutilización de los residuos orgánicos del comedor universitario de la UNT en la alimentación del ganado porcino - Bartolo García, Pedro Raúl (2014)
Food materials have been used in our country for a long time as food for pigs, but the way it is being carried out at present generates environmental problems as residues decompose rapidly producing gas, odor and onset of disease vectors. This problem coupled with the increasingly availability space in landfills does not lead to the search for new treatments and alternatives for this waste refuse. In this paper the stabilization of food waste from the UNT College Eater was evaluated, obtaining better treatment whose performance as pig feed was subsequently evaluated. Sixteen different combinations of food waste, waste silage biodiesel (ERB) and molasses were incubated 40 ° C for four days. Twelve of them were dismissed by the presence of gases, odors and greenish spots on the sample. T11, T12, T15 and T16 were treatments that showed an appropriate fermentation process, so that the stabilization of the pH for twenty days was evaluated. The four treatments had adequate fermentation, with decrease of pH less than 4 on the third day, obtaining stable values from the fifth day until day 20. Of these four treatments the T16 treatment, which had the highest percentage of ERB and molasses in its composition, which was designated as experimental food (AE) for bioassay in pigs was chosen. This product had a high moisture content (72%) so it was combined with balanced food leading to the following diets: control (0% AE), T1 (25% AE) and T2 (50% AE) assessed in 18 pigs in nine experimental units for a period of four weeks. The results of the bioassay pigs analyzed with the Tukey test (α = 0.05) showed significant differences between the weight gain of pigs with T2 (8.17 kg / week) and C (6.33 kg / wk) diets, the first which gave better results. The same behavior was observed for feed intake on a fresh basis. But to eliminate the variability caused by different levels of moisture treatments was determined that there were no significant differences in feed intake (dry basis) among the three treatments. Regarding the rate and feed conversion efficiency evaluated in fresh food base, it was determined that the control treatment was the best performer. But analyzing these indices dry basis thereof no significant differences among treatments were observed. In assessing the cost of production of each of the tested diets and average amounts of food consumed was determined that treatment T2 had the lowest cost (S /. 1.03 per kg), followed by IT (S /. 1.20 kg) and C (S /. 1.36 kg), but when considering the total cost of food consumed during the four weeks of rehearsal and subtract the gain that would be obtained by selling the meat (weight gained during the test), TI was determined that the treatment is generating increased net profit for the producer, followed by T2 and C. Additionally succeeded in evaluating the thickness of the chest fat pigs at the end of the bioassay benefit, determining that there were no significant differences in the accumulation of fat in the 3 diets fed pigs